ALL-144: Oncogenic Deregulation of BCL11B in Lineage Ambiguous Leukemia - Montefiori, Lindsey E.; Bendig, Sonja; Gu, Zhaohui; Chen, Xiaolong; Polonen, Petri; Ma, Xiaotu; Murison, Alex; Zeng, Andy; Garcia-Prat, Laura; Dickerson, Kirsten; Iacobucci, Ilaria; Abdelhamed, Sherif; et al. (Clinical lymphoma, myeloma and leukemia, 2021)
Acute leukemias of ambiguous lineage (ALAL) pose significant diagnostic and therapeutic challenges due to lack of clarity surrounding their cellular origins and driving genomic alterations, as well as poor long-term response to conventional chemotherapy. Most ALAL cases are diagnosed as mixed phenotype acute leukemia (MPAL) or acute undifferentiated leukemia (AUL); however, early T-cell precursor acute lymphoblastic leukemias (ETP-ALL, a subset of T-ALL), often express myeloid markers, suggesting a degree of lineage ambiguity. Biological distinctions between these diseases remain vague, as T/myeloid MPAL and ETP-ALL exhibit similar mutational and immunophenotypic profiles, highlighting the need for an improved understanding of ALAL etiology. To resolve biological heterogeneity of ALAL, we performed a large-scale genomic analysis, including whole-transcriptome and whole-exome/genome sequencing, of 1,114 primary leukemia samples spanning the stem, myeloid, and T lineages. Transcriptional profiling identified a group of cases (N=61) with a distinct gene expression profile that included one-third of all T/myeloid MPAL and ETP-ALL cases examined, as well as subsets of acute myeloid leukemia (AML) and AUL. Whole-genome sequencing identified structural variants targeting the T-cell transcription factor gene BCL11B in 100% of cases and FLT3 mutations in 80% of cases. Most structural variants resulted in chromosomal translocations that placed the BCL11B gene in proximity to super-enhancers active in hematopoietic stem or early progenitor cells, a cell type where BCL11B is normally repressed. Additionally, 20% of cases harbored high-copy tandem amplification of a 2.5-kb non-coding element downstream of BCL11B that we term BCL11B enhancer tandem amplification or BETA. Analysis of 3D chromatin structure in primary leukemia samples demonstrated ectopic chromatin interactions between BCL11B and rearranged hematopoietic stem/progenitor cell super-enhancers, or between BCL11B and BETA, thereby demonstrating enhancer hijacking or de novo super-enhancer formation as the mechanism of aberrant BCL11B expression in this subtype. In vitro modeling in human CD34+ stem/progenitor cells demonstrated that ectopic BCL11B expression was sufficient to upregulate T-lineage gene expression programs and block myeloid differentiation, which was exacerbated by constitutive FLT3 signaling. BCL11B deregulation in primitive hematopoietic cells is an oncogenic driver of a subset of ALAL that transcends conventional immunophenotypic distinctions.